DINAMIKA DIGITALISASI PERBANKAN - Setyanoor, Erwan (Al-Ujrah | Jurnal Ekonomi Syariah, 2023)
Human beings are social beings who fulfil needs of life and need others, and also need technology to support them. Technology in this era demands an understanding of it, so, it can be used in every sector in life. This article discusses technology in the financial and banking sectors that is very beneficial and helps in the traffic of payments, that is, digitalization, which is an application based on digital. Banking financial digitalization is the application of a digital system on payment traffic services. The digitalization of the economy in general has a huge potential and allows to reach Indonesia to go digital. The result of this writing is that the positive thing of financial digitization is economic traffic that is increasingly fast and even, making Small and Medium Enterprise (SME) more expanding, can empower human resources. This can be seen from the disabled Gojek/grab partner, which is practical and very easy. Manufacturers efficiently reduce transaction costs and make the cost of printing cartel money low. In addition, the existence of digitalization, it is making some parties lose jobs by replacing them with machines, creating new jobs and making communities with low ICT skills in trouble, becoming less competitive in business, generating new types of crime like cyber-crime, it causes the closure of bank offices, creating monetary policy implications, the risks of the IT security used, a shift in public savings, and reducing the currency component in base money